Kreativitas Desain Busana Tokoh Werkudara dalam Pertunjukan Kresnayana ke-10 - ALDEWA RISKANADI,; Yanuartuti, Setyo (Solah, 2025)
Werkudara is a character from traditional Javanese wayang (shadow puppet) stories known for his strength, spirituality, and bravery. In the 10th Kresnayana Festival held in Blitar Regency, this character was featured as the central figure, with a costume that underwent a transformation from traditional forms to a more modern and symbolic style. This study aims to describe the form and creative aspects of Werkudara’s costume design in the performance. A qualitative descriptive method was employed, using techniques such as observation, interviews, and documentation, with data analyzed through reduction, presentation, and conclusion drawing. Data validity was maintained through source and technique triangulation. The results show that Werkudara’s costume design preserved distinctive elements of Javanese culture while being modified to enhance the visual appeal of the performance and the comfort of the performer. Innovations included the use of Balinese poleng cloth, a silver cloak, and a crown resembling the Gelung Minangkara style, symbolizing strength and renewal. Thus, Werkudara’s costume in the 10th Kresnayana performance reflects both creative design and cultural preservation in a modern context.